A latitudinal diversity gradient in planktonic marine bacteria - Fuhrman, Jed A. (National Academy of Sciences, 2008)
For two centuries, biologists have documented a gradient of animal and plant biodiversity from the tropics to the poles but have been unable to agree whether it is controlled primarily by productivity, temperature, or historical factors. Recent reports that find latitudinal diversity gradients to be reduced or absent in some unicellular organisms and attribute this to their high abundance and dispersal capabilities would suggest that bacteria, the smallest and most abundant organisms, should exhibit no latitudinal pattern of diversity. We used amplified ribosomal intergenic spacer analysis (ARISA) whole-assemblage genetic fingerprinting to quantify species richness in 103 near-surface samples of marine bacterial plankton, taken from tropical to polar in both hemispheres. We found a significant latitudinal gradient in richness. The data can help to evaluate hypotheses about the cause of the gradient. The correlations of richness with latitude and temperature were similarly strong, whereas correlations with parameters relating to productivity (chlorophyll, annual primary productivity, bacterial abundance) and other variables (salinity and distance to shore) were much weaker. Despite the high abundance and potentially high dispersal of bacteria, they exhibit geographic patterns of species diversity that are similar to those seen in other organisms. The latitudinal gradient in marine bacteria supports the hypothesis that the kinetics of metabolism, setting the pace for life, has strong influence on diversity.